Desenvolvimento de um dispositivo de Movimentação Passiva Contínua Aquático para reabilitação do membro inferior humano - Borges, Isabella de Paula Cintra (2018)
The human being has always sought to perform their tasks with the least possible effort. So, with the advancement of technology, devices were emerging to simplify the execution of various tasks, reducing the time required to fulfill them, in order to improve the quality of life and facilitate rehabilitation / task execution processes. With this advance, there were robots, which currently have been widely used in health care, such as surgery, prostheses and structures that assist the rehabilitation process. This work aims to develop a Continuous Passive Motion (CPM) aquatic device for rehabilitation of the human lower limb, in order to provide a better quality of life and self-esteem of people who have suffered an injury in the leg. The aquatic environment was chosen by the advantages it presents as weight relief and safety by patients. The CPM was chosen because of the effort be external to the patient, thus enabling early rehabilitation. To achieve the objective of this work was first carried out a study on the existing CPM devices, on water, on the use of robots in rehabilitation and existing devices for the aquatic environment, was also presented a study of kinesiology and anthropometry of lower limb. After it is developed a mathematical model of the mechanism proposed in this paper, the construction of the prototype and finally the experimental tests, which presented small errors between the numerical model and experimental model.